Adatom Bonding Sites in a Nickel‐Fe3O4(001) Single‐Atom Model Catalyst and O2 Reactivity Unveiled by Surface Action Spectroscopy with Infrared Free‐Electron Laser Light. (19th May 2022) - Liu, Yun; Han, Zhongkang; Gewinner, Sandy; Schöllkopf, Wieland; Levchenko, Sergey V.; Kuhlenbeck, Helmut; Roldan Cuenya, Beatriz
Abstract: Single‐atom (SA) catalysis presently receives much attention with its promise to decrease the cost of the active material while increasing the catalyst's performance. However, key details such as the exact location of SA species and their stability are often unclear due to a lack of atomic level information. Here, we show how vibrational spectra measured with surface action spectroscopy (SAS) and density functional theory (DFT) simulations can differentiate between different adatom binding sites and determine the location of Ni and Au single atoms on Fe3 O4 (001). We reveal that Ni and Au adatoms selectively bind to surface oxygen ions which are octahedrally coordinated to Fe ions. In addition, we find that the Ni adatoms can activate O2 to superoxide in contrast to the bare surface and Ni in subsurface positions. Overall, we unveil the advantages of combining SAS and DFT for improving the understanding of single‐atom catalysts. Abstract : With surface‐sensitive action spectroscopy and DFT simulations, the binding site of Ni single atoms on Fe3 O4 (001) has been elucidated. These Ni single atoms can activate O2 to superoxide in contrast to bare Fe3 O4 (001) and subsurface Ni atoms in Fe3 O4 (001).